Jerzy Bossak. Szkic do portretu (1910–1989) - Marek Hendrykowski (Images)
The article presents a profile of Jerzy Bossak (1910–1989), an outstanding Polish filmmaker, head of the Polish Film Chronicle and the Kamera film team, and a long-time distinguished pedagogue at the Łódź Film School.